2018
DOI: 10.3382/ps/pex326
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for Welfare-Friendly Feeding of Broiler Breeders: Effects of Daily vs. 5:2 Feed Restriction Schedules

Abstract: Restricted feeding of broiler breeders is required for improved long-term health and welfare. Because feeding frustration and hunger are major welfare concerns during rearing, many suggestions have been made to decrease the negative feelings of hunger while maintaining suitable growth rates and reproductive health. Non-daily ("skip-a-day") feeding schedules are commonly used around the world to increase portion sizes at meal times while restricting intake but these practices are prohibited in many countries du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Birds fed according to the CR and IF feeding regimens showed similar growth rates, although IF-fed birds had a consistently higher feed intake as previously reported (13). It is well known that the liver is central to the primary metabolic response to dietary changes in chickens (14), and shows large fluctuations in mass, glycogen content and lipid content under IF conditions in both RJF (13) and broiler breeders (10,15). Concomitant with these overt physiological effects are large effects on hepatic transcription.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Birds fed according to the CR and IF feeding regimens showed similar growth rates, although IF-fed birds had a consistently higher feed intake as previously reported (13). It is well known that the liver is central to the primary metabolic response to dietary changes in chickens (14), and shows large fluctuations in mass, glycogen content and lipid content under IF conditions in both RJF (13) and broiler breeders (10,15). Concomitant with these overt physiological effects are large effects on hepatic transcription.…”
Section: Introductionsupporting
confidence: 61%
“…The expression of these three inflammation-associated genes could indicate either a reduced need or a reduced capacity for inflammatory responses in IF-fed birds. At this point we cannot say which of these two explanations is more likely, but it is worth noting that IF leads to a modest increase in heterophil-tolymphocyte ratios (heterophils are the avian equivalent of neutrophils in mammals) which does suggest an immune activation under these conditions (10).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that broiler breeders fed every other day, and thus given twice the amount of feed, take 2.5 times as long to finish their meals which would support the idea of reduced feed competition (Bennett and Leeson, 1989). Lower numbers of feather fault bars (Arrazola et al, 2019a) and reduced anticipatory behavior before feeding time (Lindholm et al, 2018) reported in IF-fed breeders are also suggestive of reduced competition stress in these animals. While these regimens have sometimes been criticized for imposing high stress levels on fasting days (Renema and Robinson, 2004), others have concluded that IF regimens do not increase overall stress levels compared to daily feeding as assessed by HLRs and behavioral observations (Skinner-Noble and Teeter, 2009).…”
Section: Improving the Breeder Situation: Intermittent Fastingmentioning
confidence: 84%
“…AgRP also appears to be involved in driving the increase in locomotory behaviors that is typical of feed-restricted animals in anticipation of food (Thomas and Xue, 2018). This behavior is independent of the circadian rhythm control in the suprachiasmatic nucleus (Thomas and Xue, 2018) and is also well documented in chickens (D'Eath et al, 2009;Kostal et al, 1992;Lindholm et al, 2018;Savory and Lariviere, 2000). The appetitive effects of AgRP are further supported by studies showing that presentation of food, especially if it is palatable, to a calorie-deficient rodent reduces AgRP and increases POMC expression within seconds.…”
Section: Eating Behavior and Appetite In Meat-type Chickensmentioning
confidence: 90%
“…https://doi.org/10.1101/441220 doi: bioRxiv preprint Buckley and colleagues [40], pullets under commercial feed restriction had shorter latencies than pullets fed at 80% of ad libitum feed intake in a T-maze choice test. Previous research with broiler breeders also noted that fearfulness linearly decreased as feed restriction increased [14,15] and during off-feed days under non-daily feed restriction [43]. For this reason, light broiler breeders under feed restriction conditions display high arousal as suggested by short latency and low fearfulness in behavioural tests [40][41][42], probably being less consistent in short-term choices due to previous experiences and current feeding motivation.…”
Section: Discussionmentioning
confidence: 98%